Kronecker's Limit Formula, Holomorphic Modular Functions, and q-Expansions on Certain Arithmetic Groups. Issue 3 (2nd July 2016) - Jorgenson, Jay; Smajlović, Lejla; Then, Holger
ABSTRACT: For any square-free integer N such that the "moonshine group" Γ0 ( N ) + has genus zero, the Monstrous Moonshine Conjectures relate the Hauptmodul of Γ0 ( N ) + to certain McKay–Thompson series associated to the representation theory of the Fischer–Griess monster group. In particular, the Hauptmoduli admits a q -expansion which has integer coefficients. In this article, we study the holomorphic function theory associated to higher genus groups Γ0 ( N ) + . For all such arithmetic groups of genus up to and including three, we prove that the corresponding function field admits two generators whose q -expansions have integer coefficients, has lead coefficient equal to one, and has minimal order of pole at infinity. As corollary, we derive a polynomial relation which defines the underlying projective curve, and we deduce whether i ∞ is a Weierstrass point. Our method of proof is based on modular forms and includes extensive computer assistance, which, at times, applied Gauss elimination to matrices with thousands of entries, each one of which was a rational number whose numerator and denominator were thousands of digits in length.